Pengaruh Faktor Sosial Ekonomi Petani Menggunakan Pupuk Organik pada Usahatani Sawi (Studi Kasus di Kecamatan Taebenu, Kabupaten Kupang, NTT) - Trisumarni, Ludgardis; Roy Nendissa, Doppy; P.N. Nainiti, Selfius (Journal of Agricultural Socio-Economics (JASE), 2021)
Many factors influence small farmers to use organic fertilizers in their farming. This study was to analyze the effect of the socio-economic factors of farmers using organic fertilizers on mustard farming. The data used in this study are primary data and secondary data. The method of determining the sample used a census and the determination of the research area was carried out purposively (purposive). Data analysis using binary logistic regression analysis. The results of the study found that the socio-economic factors that influenced farmers using organic fertilizers were age and income, while formal education, non-formal education, farming experience, income level, land area, production costs, and income did not affect.